On the Resolution of an Inverse Problem by Shape Optimization Techniques - Chahnaz Zakia Timimoun (Abstract and Applied Analysis)
In this work, we want to detect the shape and the location of an inclusion ω via some boundary measurement on ∂Ω. In practice, the body ω is immersed in a fluid flowing in a greater domain Ω and governed by the Stokes equations. We study the inverse problem of reconstructing ω using shape optimization methods by defining the Kohn-Vogelius cost functional. We aim to study the inverse problem with Neumann and mixed boundary conditions.